2014
DOI: 10.1002/uog.13403
|View full text |Cite
|
Sign up to set email alerts
|

Partial monochorionic and monoamniotic twin pregnancies: a report of two cases

Abstract: Monochorionic (MC) twin pregnancies are at increased CASE REPORTSThe first case was a spontaneous twin pregnancy of a 25-year-old woman, gravida 2 para 1, referred at 12 weeks' gestation for chorionicity determination. Ultrasound showed only two thin separating amniotic membranes at the lower part of the intertwin septum and one thick chorionic membrane in conjunction with two thin amniotic membranes at the upper part (Figure 1), resulting in the diagnosis of a partial monochorionic (MC) twin pregnancy. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…A study published recently (although undertaken during [2004][2005][2006] found that 19% of pathological monochorionic twins were misclassified on ultrasound, which is concerning, although the study included all ultrasound examinations performed before 20 weeks' gestation 9 . That study, in conjunction with our own case and that reported by Galjaard et al 1…”
Section: Letters To the Editor 'False' Lambda Sign In Monochorionic Tsupporting
confidence: 92%
See 1 more Smart Citation
“…A study published recently (although undertaken during [2004][2005][2006] found that 19% of pathological monochorionic twins were misclassified on ultrasound, which is concerning, although the study included all ultrasound examinations performed before 20 weeks' gestation 9 . That study, in conjunction with our own case and that reported by Galjaard et al 1…”
Section: Letters To the Editor 'False' Lambda Sign In Monochorionic Tsupporting
confidence: 92%
“…We read with interest the recent report by Galjaard et al of a case of partial monochorionic, partial dichorionic monozygotic twins 1 . Recently, we managed a related case that highlights the same clinical message.…”
Section: Letters To the Editor 'False' Lambda Sign In Monochorionic Tmentioning
confidence: 97%
“…The occurrence of partial monochorionic or partial monoamniotic twinning has also been documented, though these terms refer to incomplete septum formation secondary to the timing of zygotic cleavage. 3 Increased use of sonographic imaging for antenatal surveillance of monochorionic gestations has led to better recognition of pseudo-monoamniotic twins. However, the etiology of spontaneous rupture of the dividing membrane remains unknown due to the scarcity of this population.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent placental examination showed features in different areas in keeping with both dichorionic and monochorionic placentation. These placentas showing mixed monochorionic and dichorionic features have been described as showing hybrid chorionicity or as monodichorionic . Because of these mixed patterns, the entire dividing membrane and vascular equator should be grossly evaluated in all twins.…”
Section: Evaluation Of Chorionicity and Placental Sharementioning
confidence: 99%
“…Occasionally, the intertwin membrane in a MCDA pregnancy may become disrupted during pregnancy or during delivery, and potential remnants of this membrane should be sought. Recently, there has been a case report of a partial monoamniotic cavity where the amnion was incompletely divided . In evaluating cord entanglement in MCMA twins, certain simple procedures can be followed.…”
Section: Complications In Monochorionic Twinsmentioning
confidence: 99%